0851 Longitudinal Management of Narcolepsy with Atypical presentation of Cataplexy (unilateral with symptoms only on the right side for the past 13 years). (25th May 2022) - Pant, Alok; Ghildiyal, Naomi; Khan, Yousaf; Ho, Minh; Monceaux, Brittany; Liendo, Cesar; Chernyshev, Oleg
Abstract: Introduction: Narcolepsy with atypical unilateral cataplexy is a rare phenotype. We would like to share single center, single patient experience over the last 13 years of managing this patient. Report of Cases: 64-year-old female diagnosed with narcolepsy with unilateral cataplexy in 2008 with MSLT. Her cataplexy syndrome has been atypical, in that it has a strictly unilateral presentation for the past 13 years, with right face, arm, and leg weakness with strong emotions(anger/laughter). Her right-side extremities go limp for a few seconds to a minute. Her cataplexy syndrome has never evolved to become bilateral or unilaterally on her left side. Her physical examination has been largely unremarkable. For Narcolepsy, was on Modafinil (2008) which was up titrated to 600 mg with no side effects, eventually switched to Armodafinil 250 mg (2013). Eventually did not control EDS fully, methylphenidate (2014) was added. The patient reported cognitive impairment with gradual memory loss on stimulants (starting in 2012) and nocturnal insomnia on methylphenidate SR. Due to worsening cognition and memory, stimulants were discontinued in 2014 and patient referred to neurology and had neuropsychiatric evaluation for memory loss. Dementia lab workup and MRI with spectroscopy were unremarkable. Due to continuation of EDS was restarted on Modafinil until May 2021. In May 2021, she reported no longer fully controlled daytime sleepiness and Pitolisant was added with improvement in ESS from 17/24 to 9/24. For the management of unilateral cataplexy, patient was well controlled initially on venlafaxine (2008), eventually up titrated with an additional dose a few times. After cognitive impairment, patient stopped refilling it in 2014 and subsequently slept better without the venlafaxine. She reported that she would fall when she got very upset/mad so learnt not to get mad at people. She had many episodes of unilateral cataplexy mainly with laughing or excitement so was started on Fluoxetine 20 mg and eventually up titrated to 40 mg. Her unilateral cataplexy symptoms have been well controlled with the addition of Pitolisant. Conclusion: Management of Narcolepsy with atypical unilateral cataplexy is challenging and requires use of multiple medications with different sites of action. Support (If Any):